Parenting Program: Its Impact on Students' Religious Character in Integrated Islamic Elementary Schools - susanto, susanto -; Kholid, Idham; Amriyah, Chairul (Journal of Advanced Islamic Educational Management, 2022)
An effective public health approach can help evaluate the effectiveness of parenting programs in reducing child maltreatment. Parenting can show effectiveness in improving children's emotional and behavioral adjustment. Parenting programs are useful for parents to add insight and awareness about appropriate child development. The purpose of this study was to determine the effect of the parenting program on the religious character of students at Ar Rahman Jati Agung integrated Islamic elementary school. The method used is quantitative method. The sampling technique used. Purposive sampling. Data collection methods are questionnaires and documentation. The results of the f test simultaneously sig value 0.001 <0.05 and the value of f count 8.469> 3.16, then there is an influence of the parenting program and parenting on the religious character of students at SDIT Ar Rahman Jati Agung. The coefficient of determination test results show 22% which means that the effect is in the low category.